INVESTIGATION OF THE INTERVAL DYNAMIC SYSTEMS BEHAVIOR AND SYNTHESIS OF THEIR CHARACTERISTIC POLYNOMIALS ON THE BASIS OF THE SYSTEM ROOT LOCUS PORTRAITS PARAMETER FUNCTION APPLICATION - A. A. Nesenchuk (Informatika)
Investigation of the 4th power dynamic systems behavior in conditions of the interval parameter variations is carried out on the basis of root locus portraits. Investigation of the system dynamics is carried out and the behavior regularities at the system stability bound are determined for root locus portraits of the 4th power systems with interval parametric uncertainties. On this basis the stability conditions are derived and expressions are determined for calculating intervals of parameter variation ensuring the system robust stability.